Generative artificial intelligence as a tool for psychological and motivational support in foreign language learning - Gulich, Olena; Chetveryk, Victor (Educational Challenges, 2025)
Introduction. The rapid integration of generative artificial intelligence (AI) into education has transformed approaches to foreign language teaching and learning. Generative AI systems such as ChatGPT, Claude, Gemini and DeepSeek function not only as tools for linguistic practice but also as instruments of psychological and motivational support, creating emotionally safe and adaptive learning environments. Purpose. The purpose of this article is to examine the psychological and motivational effects of generative AI on foreign language learners and to identify the benefits and challenges of its pedagogical implementation. Methodology. The study is based on a systematic review and qualitative analysis of recent scholarly sources (2020–2025) that explore the role of generative AI in education. Comparative and analytical methods were applied to examine empirical data and theoretical perspectives concerning students’ motivation, emotional well-being, and learning outcomes when using AI-driven tools. Results. The analysis of recent studies demonstrates that the use of generative AI significantly enhances students’ engagement, intrinsic motivation, and communicative confidence while reducing language anxiety. Adaptive feedback and personalized interaction foster self-regulation, autonomy, and a growth-oriented mindset. Empirical data confirm that AI-supported learning environments satisfy learners’ psychological needs for competence, autonomy, and social connection, contributing to sustainable motivation and improved learning outcomes. Discussion. Despite its advantages, the use of AI-based tools poses several challenges, including overreliance on technology, diminished critical thinking, potential inaccuracies in generated content, and privacy concerns. To ensure the ethical and effective integration of AI into language education, it is essential to maintain pedagogical balance, promote digital literacy, and view AI as a supportive rather than substitutive element of the learning process. Conclusion. Generative AI can serve as a powerful pedagogical resource that fosters emotional well-being, motivation, and learner autonomy when implemented within a human-centered and ethically responsible framework.